Production of Dried Roasted Watermelon (Citrullus Lanatus) Seed - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2016)
Watermelon seeds are a source of protein, B vitamins, and minerals. The watermelon seeds are often discarded while the fruit is eaten. Watermelon seeds are considered as a good source of food for human nutrition and health. Drying and roasting are the most important processes giving necessary alterations to the product. Roasting can enhance flavour through caramelization on the surface of the food. There was no any research mentioned to varify the change of antioxidant (tocopherol) during infrared drying as well as storage. So the objective of the present study was to identify the effect of temperature in infrared drying, roasting condition, packaging and storage to tocopherol, total phenolic and antioxidant activity in the dried roasted watermelon (Citrullus lanatus) seed. Results demonstrated that drying temperature (45 oC), roasting (165 oC in 3 min), vaccum packing in polyethylene (PA) bag and keeping in 4 oC were recommended to maintain the tocopherol, total phenolic and antioxidant activity in the final products for 16 weeks. The effect of drying, roasting temperature and time were clearly demonstrated to produced dried roasted watermelon seed.Keywords: Watermelon seed, Drying, Roasting, Antioxidant, tocopherol, Phenolics, vaccum.